Network Attached Storage (NAS) Berbasis Raspberry Pi Di Laboratorium Jaringan Komputer Politeknik Negeri Bengkalis - Wahyat; Ryci Rahmatil Fiska; Vika Fauziah; Ryan Aprizar (ABEC Indonesia, 2022)
Computer laboratories at universities, especially vocational campuses, are very important because they function as a support for practicum courses. Today's data storage systems continue to grow, one of which is network attached storage (NAS), NAS is a storage device system that is connected to a computer network that uses the system. special operations to serve the needs of files and data files. In this study, a NAS-based centralized data storage system with Raspberry Pi will be built to support lectures in a computer network laboratory, currently the distribution process for lecture materials is carried out with a flash drive so that it is less effective and efficient, so a NAS is proposed in order to facilitate data exchange between lecturers and students. , students can access lecture materials that have been shared by lecturers and can collect practical reports on practical results. The NAS system that was built can be accessed via a personal computer/laptop with each student's name on the local network in the computer network laboratory